Research on the Impact of Artificial Intelligence on International Trade —— Taking Alibaba International Station's Foreign Trade AI as an Example - Piao, Yixin (Transactions on Economics, Business and Management Research, 2024)
This article delves into the profound impact of artificial intelligence (AI) on international trade. By reviewing the historical evolution of AI and its related policy frameworks, this research gained a clear understanding of its potential applications in international trade. Subsequently, by examining the shortcomings of traditional trade models and the evolving global economic landscape, this paper analyzes the unique advantages of AI in enhancing trade efficiency and optimizing trade structures. Taking the AI-powered foreign trade platform of Alibaba International Station as a case study, this article dissects its internal driving forces and the external factors that facilitate its development. Through an in-depth examination of its operational model, it leverages intelligent technologies to streamline trade processes, reduce costs, and introduce its primary functions and practical applications in international trade. Furthermore, this paper explores both the benefits and challenges of integrating AI into international trade, offering guidance for newcomers in the foreign trade industry on incorporating AI into their business practices. This includes advice on technology, talent development, and strategic planning.